MENIMBANG ISTIHSAN SEBAGAI DALIL LEGALITAS DALAM MUAMALAH - Muhajirin Muhajirin (Tatar Pasundan: Jurnal Diklat Keagamaan, 2022)
The Istihsan method is a legal argument whose existence is not agreed upon by ushul scholars, so the legality of the law born from this method has been debated until now. The research method used is normative juridical, which is literature study. The approach used is by comparing between the opinions of Mutakallimin and Fuqaha. Researchers conclude that The Istihsan actually has a strong foundation from both the Qur'an and al-Hadith. Its existence is an independent syara', that it can be implemented in actual problems, notably in the field of muamalah. The difference of opinion among Ushul scholars about to have Istihsan or not actually goes back to the standard of Urf as one of Istidlal methods. Implementing the method in the field of muamalah (Islamic Economy) can be found within contract of Salam, Istishna' and sale and purchase (Bai' al-Taqsith or Bai' bi Tsaman al-'Ajl). Keywords: istihsan; salam; istshna'; bai' al-taqsith.